MENGIDENTIFIKASIKAN RELEVANSI STUDI ISLAM TERHADAP PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) - Bayu Bambang Nurfauji; Murni Anjani; Rd. Putri Harisma Devi; Shanty Elisabeth Sabrina; Yuyun Yunengsih (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
Increasingly complex learning demands lead to reduced activities related to Islamic values in early childhood. Meanwhile, the education of Islamic religious values in early childhood is a very important foundation as a laying of the religious foundation so that they become devout individuals of worship. This study aims to analyze the value of Islam in early childhood. The research method used in this research is literature review by collecting data from scientific papers and previous research. The results showed that the value of the Islamic religion can be instilled through habituation and exemplary activities. Therefore, as a teacher and a parent, we must strive to have a good personality that can be used as an example as a role model for children. Teachers and parents should always improve their knowledge, understanding and skills related to the development of Islamic religious values in early childhood